Issues relating to contract administrator's instruction - Khiyon, Noor Azeyah (2011)
Contract Administrator is an employer’s agent who is engaged primarily to ensure that the works are executed effectively and economically but he is not a party to a construction contract and has no authority to instruct contractor. Thus, express provisions are included in the contract to give contract administrator power to issue instructions to contractor. Contract administrator’s instruction is very important in a construction contract and due to its importance, any issues relating to the instructions may lead to many disputes in construction contract. Therefore, this research seeks to identify issues that commonly arise relating to contract administrator’s instructions. An analysis of four selected legal cases is conducted to review the facts and the decision of the courts on the matters of contract administrator’s instructions. From the analysis, it is found that the issues that commonly arise relating to contract administrator’s instructions are non issuance of instructions, incomplete instructions, instructions are outside the scope provided by the contract and informal instructions. Therefore, parties in a construction contract must be aware of these issues in order to reduce or eliminate the effects that might occur due to it.